Faktor-Faktor yang Memengaruhi Continuance Use Intention Aplikasi Shopee Partner pada Mitra UMKM di Jabodetabek - Arsanti Raissa Kinanti; Ryna Parlyna; Osly Usman (Indo Publishing, 2026)
This study aims to analyze Continuance Use Intention among Shopee Partner users in the Jabodetabek area. This application is used by Shopee Food partners to manage their business operations digitally. This study examines the influence of System Quality, Information Quality, Service Quality, Perceived Usefulness, and User Satisfaction. Data were collected from 260 SME operators via a questionnaire and analyzed using SEM-PLS with SmartPLS 4.0 software. The results of the analysis indicate that System Quality, Information Quality, and Service Quality have a positive and significant effect on Perceived Usefulness. Service Quality and Perceived Usefulness have a positive effect on User Satisfaction, while System Quality and Information Quality do not affect User Satisfaction. Furthermore, Perceived Usefulness and User Satisfaction have a positive effect on Continuance Use Intention. Future research is recommended to expand the sample size, add variables, and use a longitudinal approach to obtain more comprehensive results.